J MATERN CHILD HEALTH 2016
DOI: 10.26911/thejmch.2016.01.03.01
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Psychological Factors and Workload on Midwife Performance in the Integrated Antenatal Care in Pati, Central Java

Abstract: Background: One of the sensitive population health indicators is maternal mortality rate (MMR).One of the MMR determinants is antenatal care (ANC) coverage. This study aimed to determine the effect of psychological factors and workload on midwife work performance in the integrated antenatal care in Pati, Central Java. Subjects and Method: This was analytic observational study with cross sectional design. This study was conducted in Pati, Central Java. A total of 130 midwives was selected for this study by stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The results of the study were in line with the results of Marfu'ah et al (2016) which states that the higher the workload of midwives, the lower the performance shown. A heavy workload will cause various effects such as physical and mental fatigue, and other emotional reactions.…”
Section: The Effect Of Workload On the Per-supporting
confidence: 87%
See 1 more Smart Citation
“…The results of the study were in line with the results of Marfu'ah et al (2016) which states that the higher the workload of midwives, the lower the performance shown. A heavy workload will cause various effects such as physical and mental fatigue, and other emotional reactions.…”
Section: The Effect Of Workload On the Per-supporting
confidence: 87%
“…The results of the 2015 Population Survey (SUPAS) reported that MMR in Indonesia amounts to 305 maternal deaths per 100,000 live births. The high level of MMR in Indonesia has made the government make efforts to reduce it as a priority program in health development (Marfu'ah et al, 2016). The number of MMR in East Kalimantan Province in 2016 was 100 per 100,000 live births.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, motivation was found to affect the MMR (P-value=.001) and IMR (P-value=.016). Midwives who had motivation to work better for any given tasks and job responsibilities had better performance than those with low motivation (Marfuah, Tamtomo and Suryono, 2016). Djunawan and Haksama (2015) also found motivation variable significantly contributed to midwife performance in antenatal services.…”
Section: Resultsmentioning
confidence: 91%
“…They must compete with other midwives, touch the hearts of the community by providing sincere service, and behave innovatively to suit community needs. Midwives' performance is mostly measured based on their capacity as government employees in hospitals or health centers or as employees in private hospitals (Kool et al, 2023;Marfu'ah et al, 2016). Midwives who practice independently are rarely researched or often marginalized.…”
Section: Introductionmentioning
confidence: 99%